PENINGKATAN KEMAMPUAN MENULIS PARAGRAF DEDUKTIF MELALUI METODE DRILL SISWA KELAS III C SD NEGERI 006 KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Lisnarwati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This research is based on the low ability to write deductive paragraph, the average result of deductive paregrat writing ability obtained by students is 27,55 or with failure category. To improve the learning outcomes, the researcher performs improvement research by applying the drill merode. This research is a classroom action research conducted in class III C SD Negeri 006 Kubang Jaya, Kecamatan Siak Hulu, Kabupaten Kampar, this research is done in two cycles, using four stages: planning, implementation, observation and reflection. The result of research stated that the ability of writing paragraphs and learning activities has increased, in cycle I the activity of teacher get score 28 (46,6%), in cycle II activity of teacher have increase with score 57 (95,00%), while in activity of sisswa in cycle I get score 1395 (80,20%), in cycle II student activity have increase with score 1478 (84,90%). The ability to write a deductive paragraph of students also experienced an increase, in the first cycle average writing ability of students is 43.89 with the category less, and in the second cycle average writing ability of students is 68.03 with enough category. Based on the results of this study can be concluded that the ability to write a paragraph deductive students class III C SD Negeri 006 Kubang Jaya, Kecamatan Siak Hulu, Kabupaten Kampar, increased after applied drill method.